Rancangan Sistem Monitoring Suhu dan Kelembaban Perangkat Set Top Box pada Internet Protocol Television Mengunakan Jaringan Local Area Network (LAN) - Yuyun Suprapto; Nur Alviani Kurnia; Totok Warsito; Moch. Rifai (Jurnal Penelitian)
This design was created to facilitate the monitoring the factor of the internet protocol television damage through technician server room. Cause of damage factor that will be monitoring are temperature, humidity and voltage on the device. Component used to monitoring the temperature and humidity is DHT22 sensor on the set top box device on internet protocol television. Basic concept of this design is DHT sensor will send the information about temperature and humidity alteration to Arduino UNO that will be processed by Arduino UNO. Data received from sensor processed by Arduino UNO and sent by ethernet shield to computer server. It will be discussed more clearly in this paper and more completely about the work principle of monitoring set top box system design on internet protocol television.